2005
DOI: 10.1128/cdli.12.12.1429-1436.2005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antigen-Specific Th1-Type Immune Responses by Gamma-Irradiated RecombinantBrucella abortusRB51

Abstract: Brucella abortus strain RB51 is an attenuated rough mutant used as the live vaccine against bovine brucellosis in the United States and other countries. We previously reported the development of strain RB51 as a bacterial vaccine vector for inducing Th1-type immune responses against heterologous proteins. Because safety concerns may preclude the use of strain RB51-based recombinant live vaccines, we explored the ability of a gamma-irradiated recombinant RB51 strain to induce heterologous antigen-specific immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 30 publications
3
38
1
Order By: Relevance
“…It is noteworthy that irradiated Brucella demonstrated enhanced protection compared to metabolically inactive heat-treated bacteria. Our results are consistent with previous reports using gamma-irradiated B. abortus strain RB51 and gamma-irradiated Listeria monocytogenes (13,38) Importantly, different approaches generating nonreplicating metabolically active organisms result in effective protection against intracellular pathogens (8,13,23,38). Together, these findings suggest that despite the inactivation method, metabolic activity is the key component mediating effective immunity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is noteworthy that irradiated Brucella demonstrated enhanced protection compared to metabolically inactive heat-treated bacteria. Our results are consistent with previous reports using gamma-irradiated B. abortus strain RB51 and gamma-irradiated Listeria monocytogenes (13,38) Importantly, different approaches generating nonreplicating metabolically active organisms result in effective protection against intracellular pathogens (8,13,23,38). Together, these findings suggest that despite the inactivation method, metabolic activity is the key component mediating effective immunity.…”
Section: Discussionsupporting
confidence: 83%
“…Irradiation has long been used as a method to prevent mammalian cell proliferation without inhibition of cellular activity (39). Irradiated microorganisms also retain metabolic activity, as suggested by researchers utilizing the irradiated bacteria B. abortus strain RB51 (38). Furthermore, other researchers demonstrated that the gamma-irradiated protozoan Toxoplasma gondii retains "morphology, metabolism, and cell invasion properties," suggesting that the cellular functions were not abrogated by irradiation (19).…”
mentioning
confidence: 93%
“…Therefore, we used exposure to a minimum dose of gamma radiation as a means to abolish the ability of B. neotomae to replicate. The use of ionizing radiation has been used in the development of vaccines for preventing infectious diseases of animals and humans that are caused by different viruses, bacteria, and parasites [13, 25-29]. However, a recently developed strategy specifically uses exposure to a minimum dose of radiation, which is sufficient to abolish replication of the organism, for developing safer vaccines for diseases caused by intracellular pathogens [13, 28-29].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ionizing radiation has been used in the development of vaccines for preventing infectious diseases of animals and humans that are caused by different viruses, bacteria, and parasites [13, 25-29]. However, a recently developed strategy specifically uses exposure to a minimum dose of radiation, which is sufficient to abolish replication of the organism, for developing safer vaccines for diseases caused by intracellular pathogens [13, 28-29]. Similar to the previously reported findings for B. abortus RB51 and B. melitensis Rev1 [13, 29], B. neotomae exposed to a minimum of 300-350 krads of radiation lost its ability to replicate on nutrient rich TSA medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation